Video-Based Learning on Plant Reproduction using Panca Pramana in Science Content to Stimulate Critical Thinking Skills in Students - Sari, Ni Made Anggreni Nopita; I Gede Astawan; Gusti Ayu Putu Sukma Trisna (Universitas Pendidikan Ganesha, 2024)
Critical thinking skills are essential abilities that students must possess to address various problems in life, including understanding scientific concepts. However, students' critical thinking skills in science subjects remain relatively low, coupled with the suboptimal use of digital learning media in the classroom. This study aims to analyze the effectiveness of a plant reproduction learning video based on the Panca Pramana concept in stimulating students' critical thinking skills. This research employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 31 fourth-grade students. Data were collected through questionnaires and critical thinking tests, with instruments in the form of questionnaires and essay tests. Data analysis was performed using a paired sample t-test at a 5% significance level. The results showed a significance value (2-tailed) of 0.001 (p < 0.05), indicating a significant difference before and after the implementation of the learning video. These findings suggest that the Panca Pramana-based learning video is effective in stimulating students' critical thinking skills. The implication of this study is that teachers can adopt this video as a reference for developing innovative and contextual digital learning media to enhance science learning quality in elementary schools.